Direct-Driven Blade-Embedded Pitch Actuator for High Dynamic Pitching Applications (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The efficiency of vertical-axis cross-flow turbines can be significantly improved by actively adjusting the pitch during each rotation cycle. This continuous pitching of the blade demands a high dynamic actuator, which in turn should not perturb the flow, for instance, by embedding it into the blade. These requirements and conditions make the design challenging. The usual approach using conventional servo motors with a gearbox has the disadvantage of wear, increased by frequent changes in motion direction, and backlash, which may lead to inaccurate position control or even instability. To avoid this, in the present work, a direct-driven actuator with a form factor suited to embed it into a blade profile is proposed. A parametric FEM model was developed and a prototype was implemented to validate the proposal. A cascaded position control algorithm was also designed and implemented. It can be seen that, although the torque characteristic varies with the angle, it still meets the requirements for the expected pitch span. Finally, using the proposed controller, the ability to track the pitch angle with expected high accuracy and dynamics has been demonstrated.